2016
DOI: 10.3171/2015.12.peds15600
|View full text |Cite
|
Sign up to set email alerts
|

Macrocephaly in infancy: benign enlargement of the subarachnoid spaces and subdural collections

Abstract: OBJECTIVE Benign enlargement of the subarachnoid spaces (BESS) is a common finding on imaging studies indicated by macrocephaly in infancy. This finding has been associated with the presence of subdural fluid collections that are sometimes construed as suggestive of abusive head injury. The prevalence of BESS among infants with macrocephaly and the prevalence of subdural collections among infants with BESS are both poorly defined. The goal of this study was to determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
50
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(56 citation statements)
references
References 12 publications
1
50
0
5
Order By: Relevance
“…The proposed mechanism for subdural bleeding with enlarged subarachnoid spaces is similar to the mechanism proposed for GA1and for D2-HGA Type II, whereby the bridging veins spanning this enlarged subarachnoid space are under increased tension and are, as a result, more susceptible to shear forces from minor trauma or in the absence of trauma by way of typical child handling. 5,7,10…”
Section: Discussionmentioning
confidence: 99%
“…The proposed mechanism for subdural bleeding with enlarged subarachnoid spaces is similar to the mechanism proposed for GA1and for D2-HGA Type II, whereby the bridging veins spanning this enlarged subarachnoid space are under increased tension and are, as a result, more susceptible to shear forces from minor trauma or in the absence of trauma by way of typical child handling. 5,7,10…”
Section: Discussionmentioning
confidence: 99%
“…(10) A relatively common presentation is the Benign Enlargement of the Subarachnoid Space (BESS) or benign external hydrocephalus, that is asymptomatic and usually resolves spontaneously before the child reaches the age of two years. (11,12) Most hydrocephalus patients though, present with symptoms, but not necessarily the well-known acute symptoms of increased intracranial pressure or an obviously increased head circumference. They may just as well be presenting with normal or only slightly increased head circumference, and variable degrees of psycho-motoric delay or failure to thrive during infancy.…”
Section: Introductionmentioning
confidence: 99%
“…7 Recent studies reported infrequent presence of SDH=SDC among children with BEH=BESS; that is, SDC was seen among 5.6% of 108 children with BESS 8 and 5.8% of 311 imaging studies of children with BESS. 9 As Ulf et al mentioned, we cannot deny the possibility of over-diagnosing possible AHT due to limitation of using available ICD-10 codes from DPC database. Considering the incidence rate of BEH=BESS, 4 there might be approximately 400 children with BEH=BESS born each year because the annual number of live births is about one million in Japan.…”
mentioning
confidence: 97%